PENGEMBANGAN SISTEM INFORMASI PENYALURAN BANTUAN BERBASIS WEBSITE STUDI KASUS BALAI PENYULUHAN PERTANIAN KECAMATAN KEMPO - Mantika, Salsabilla; Murpratiwi, Santi Ika; Afwani, Royana (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2025)
The agricultural sector is a key pillar of Indonesia's economy, including in West Nusa Tenggara (NTB) Province. According to 2023 census data from the Central Statistics Agency (BPS), 768,765 farmers are engaged in Individual Agricultural Enterprises (UTP), with 46,910 from Dompu Regency, linked to the Agricultural Extension Center (BPP). BPP Kempo District faces inefficiencies in aid distribution due to manual processes using books and paper, leading to data recording errors. To address this, a web-based aid distribution information system was developed, providing aid registration and announcement features to facilitate data management and communication. This study aims to enhance aid distribution efficiency by digitizing manual processes. The Prototyping method was applied to allow early user feedback, ensuring improvements before the final system deployment. This approach helps minimize errors and aligns the system with user needs. The results, based on black-box testing and User Acceptance Testing (UAT), confirm the system's effectiveness. Black-box testing with end users verified that all features met expectations, while UAT showed an 87.95% satisfaction rate, categorized as